Glycemic responses of three mango varieties in subjects with and without T2D: a pilot crossover study using OTT and CGM - Kehar, Sugandha; Bhatt, Surya Prakash; Pandey, Ravindra M; Ahmad Ansari, Irshad; Palavalli, Rajashekar Reddy; Gupta, Vimal; Misra, Anoop (European journal of clinical nutrition, 2025)
Mango consumption is often restricted in diet consumed by people with diabetes due to concerns about its glycemic impact. This study aimed to compare the glycemic effects of mango consumption with those of white bread and glucose in subjects with and without type 2 diabetes (T2D). We conducted a two-phase study involving 95 participants (45 with T2D, 50 non-diabetic). Phase 1 employed oral tolerance test (OTT) to assess immediate glycemic responses to mango (Safeda, Dasheri, and Langra), bread, and glucose. Phase 2 utilized continuous glucose monitoring (CGM) to evaluate glycemic profiles over three days. On OTT, in non-diabetic subjects, mango consumption resulted in non-significantly lower postprandial glucose peaks compared to glucose and bread, except Langra variety which showed lowest area under the curve for glucose of borderline significance. In subjects with T2D, mango varieties performed similarly to bread. CGM data revealed that mango consumption over three days resulted in a similar glycemic profile to bread in non-diabetic subjects and a lower glycemic profile in subjects with T2D, though most differences were statistically not significant. Mean Amplitude of Glycemic Excursion (MAGE) was significantly lower after mango ingestion as compared to bread in CGM data in subjects with T2D. Data show limited glycemic impact of tested mango varieties, comparable to or lower than white bread, especially in T2D subjects. The significant reduction in MAGE observed with mango consumption suggests potential benefits for glycemic variability. With portion control in calorie restrictive diets, mango may be suitable for people with T2D.